Data from Black and White Layers - Swart, Peter; Mackenzie, Greta; Eberli, Gregor; Blattler, Clara; Nakakuni, Masatoshi; Betzler, Christian (IEDA: EarthChem Library, 2020)
Abstract: This dataset reports carbon and nitrogen isotopic composition and the C/N ratio of the organic material present in the newly discovered occurrence of thick sequences (∼100 m) of Late Oligocene and Early Miocene (∼24.9 to ∼20 Ma) interbedded organic-rich sediments (sapropels) and pelagic (organic poor) carbonates at Sites U1466 and U1468 drilled in the Maldives archipelago during the International Ocean Discovery Program (IODP) Expedition 359. Other Description: Swart, P.K., Blättler, C.L., Nakakuni, M., Mackenzie, G.J., Betzler, C., Eberli, G.P., Reolid, J., Alonso-García, M., Slagle, A.L., Wright, J.D., Kroon, D., Reijmer, J.J.G., Hui Mee, A.L., Young, J.R., Alvarez-Zarikian, C.A., Bialik, O.M., Guo, J.A., Haffen, S., Horozal, S., Inoue, M., Jovane, L., Lanci, L., Laya, J.C., Lüdmann, T., Nagender Nath, B., Niino, K., Petruny, L.M., Pratiwi, S.D., Su, X., Sloss, C.R. and Yao, Z. (2019) Cyclic anoxia and organic rich carbonate sediments within a drowned carbonate platform linked to Antarctic ice volume changes: Late Oligocene-early Miocene Maldives. Earth Planet. Sci. Lett. 521, 1-13.